Economic Impact Among Family Caregivers of Patients With Advanced Ovarian Cancer. Issue 8 (October 2015) - Angioli, Roberto; Capriglione, Stella; Aloisi, Alessia; Miranda, Andrea; de Cicco Nardone, Carlo; Terranova, Corrado; Adrower, Roberto; Plotti, Francesco
<x xml:space="preserve">Abstract</x> Objectives The life of a family caregiver changes in many ways when cancer is diagnosed. Changes regard also financial costs. To the authors' knowledge, little work has been done to estimate the costs associated with caregiving for cancer patients. The aim of the present study is to evaluate for the first time in literature the economic changes among family caregivers of advanced ovarian cancer during the first-line treatment in an Italian survey. Methods Between January 2009 and June 2014, the primary family caregivers of patients with advanced ovarian cancer (N = 172) were recruited from to the Division of Gynecologic Oncology of the University Campus Bio-Medico of Rome within 4 weeks of the patient's new diagnosis. Caregivers reported demographic, medical information, and economic cost, such as traveling to and from medical appointments, waiting with patients for appointments, missing work, and attending to patients who are hospitalized. Results Between January 2009 and June 2014, 172 primary family caregivers of patients with advanced ovarian cancer were enrolled in the study. The mean age of the study cohort was 54.01 years. They reported 3% of missing workdays. The mean cost for all caregivers was [Euro sign]1, 888, 732 per year. Therefore, the mean cost for each caregiver was [Euro sign]10, 981 annually. Conclusions This economic analysis of caregiving in patients with advanced ovarian cancer reports the significant burden that cancer treatment places on both families and society. These findings underscore the importance, when appropriate, of including valid estimates of the cost of informal caregiving when evaluating the cost-effectiveness of cancer treatments.